Ethnicity and Religion: The Twin Identity Challenge to Nigerian Integration Drive - Hassan, Salisu Inusa; Babayo, Adamu; Kashere, Dauda Yahaya (Kashere Journal of Politics and International Relations, 2023)
Nigeria as Africa’s most populous country and biggest black nation in the world, is an ethnically and religiously diverse country encompassing of well over 250 ethnic nationalities belonging to about 350 spoken languages who majorly religions of Islam, Christianity and traditional followers. This paper examined the challenge posed by ethnicity and religious identity towards Nigerian integration drive. The ethnic groupings are not uniformly spread, hence, have a differential level of power and influence. Invariably, three major ethnic groups constitute two-thirds of the country’s population among who are the predominantly Christian Igbo in the South East, the majority Muslim Hausa, Kanuri, Nupe and Fulani in the North (often lumped as Hausa/Fulani) and the religiously mixed Yoruba in the South West. Within the midst of the three major ethnic groups, the remaining one-third coexists, thereby opening up the vista of agitations by the minority groups against the domineering tendencies of the trio numerically advantaged. What is more glaring is the political space provided by democratic practice to select and elect political representatives in the federation at all levels. The level of competitive democracy and power seeking of the political elite since 1999, have left much to be desired, who exploited gullible Nigerians by dividing them on ethno-religious fault lines. This paper seeks to analyze the identity pogrom of Nigeria as it relate to democratic practice and political integration.